Anticataract activity of Erythrina stricta against naphthalene-induced cataractogenesis in rats - Muthuswamy Umamaheswari, Kuppuswamy Asokkumar, Andichettiyar Thirumalaisamy Sivashanmugam, Varadharajan Subhadradevi and Michael Neethu (Bangladesh Pharmacological Society, 2010)
The anticataract activity of Erythrina stricta leaves against naphthalene-induced cataractogenesis was studied in Wistar albino rats. The various fractions of the leaf extract were administered orally (200 mg/kg) simulta-neously with naphthalene (1 g/kg) for 28 days. At the end of the experiment, levels of malondialdehyde, lipid hydroperoxides, carbonyl and sulfhydryl content, enzymatic and non-enzymatic antioxidants in lens homogenate were measured. Administration of naphthalene produced a mature cataract and an increase in the opacity index. There was a significant increase in lipid peroxidation and a decrease in antioxidant enzymes when compared to normal control. Ophthalmoscopic observation indicated that simultaneous administration of the fractions delayed the onset and maturation of cataract. All the fractions (except the residual fraction) prevented the peroxidative damage caused by naphthalene. The leaves of E. stricta protected the lens against naphthalene damage which may be due to its antioxidant activity.